DEVELOPING CEFR ILLUSTRATIVE DESCRIPTORS OF ASPECTS OF MEDIATION - Brian North (Informascope, 2016)
Mediation is not concerned with the linguistic expression of a speaker. Instead, the focus is on the role of language in processes like creating the space and conditions for communication and/or learning, constructing new meaning, encouraging others to construct or understand new meaning, passing on information in an appropriate form, and simplifying, elaborating, illustrating or otherwise adapting input in order to facilitate these processes (mediation strategies). Mediation always involves bridging across spaces, facilitating understanding. The context can be social (e.g. Wall & Dunne 2012), pedagogic (e.g. Mercer & Hodgkinson 2008), cultural (e.g. Zarate et al 2004), linguistic (e.g. Statholopoulou 2015) or in the workplace (e.g. Lüdi 2014). The concept of mediation has a very long history, originating in acting as an intermediary in diplomacy and conflict resolution, developing into wider forms of conflict avoidance and counselling services. Its relevance to the educational domain derives from Vgotsky's (1978) theories, in which, it is seen as a core feature when adults, siblings and peers interact with a child. In the resulting socio-constructivist / social cultural view of learning (Lantolf 2000) it has recently been developed into the concept of 'languaging' in order to mediate meaning, a process that takes two forms: collaborative dialogue and private speech (Swain, Kinnear & Steinman, 2015: 32). The latter concerns the individual mediating meaning for themselves and is often internal and invisible. It is the former with which we are primarily concerned in this article. Collaborative dialogue in fact already appears in the Common European Framework of Reference for Languages (CEFR: Council of Europe 2001) in the scale under interaction strategies for Cooperating. In addition, the emphasis in the CEFR on the mediator as an intermediary between different interlocutors underlines its social, collaborative vision of language (Piccardo 2012).